2015
DOI: 10.1681/asn.2015030252
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Modifies the Paradoxical Association between Body Mass Index and Mortality in Hemodialysis Patients

Abstract: High body mass index (BMI) is paradoxically associated with better outcome in hemodialysis (HD) patients. Persistent inflammation commonly features in clinical conditions where the obesity paradox is described. We examined the relationship between BMI and mortality in HD patients, accounting for inflammation, in a historic cohort study of 5904 incident HD patients enrolled in 2007-2009 (312 facilities; 15 European countries) with $3 months of follow-up. Patients were classified by presence (n=3231) or absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
80
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 56 publications
11
80
0
4
Order By: Relevance
“…The findings of this paper, using observational data, suggest that weight loss may have potential advantages for obese patients on dialysis without evidence of inflammation. 8 This finding should be confirmed in intervention studies before incorporation into clinical practice.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…The findings of this paper, using observational data, suggest that weight loss may have potential advantages for obese patients on dialysis without evidence of inflammation. 8 This finding should be confirmed in intervention studies before incorporation into clinical practice.…”
mentioning
confidence: 84%
“…3 In this issue of the Journal of the American Society of Nephrology (JASN), results of a large cohort study have shown a novel important aspect of obesity-the effect modification by inflammation. 8 Stenvinkel et al 8 found that the paradoxical association between BMI and mortality in patients that required hemodialysis was modified by inflammation. Stenvinkel et al 8 studied 5904 patients with incident hemodialysis from 15 European countries that were enrolled in the study in 2007-2009.…”
mentioning
confidence: 99%
See 3 more Smart Citations